RELEVANCE AND IMPORTANCE OF ENSURING THE SECURITY OF INFORMATION IN NETWORKS - Ibragimov Nodirjon Nusriddinovich; Abdurakhmanov Vahid Abdumuqim Oglu; Amirov Akbarshokh Dilshod son; Shukurova Sitora Zayir qizi; Gulboeva Sabrina the Gofur girl (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes such concepts as the concept of information, types of information, threats to information security and their types, the importance of Information Security. Threats to Information Security have been interpreted on modern grounds.